A Case of Nonuremic Calciphylaxis in a Caucasian Woman - Bonnie Fergie; Nishant Valecha; Andrew Miller (Case Reports in Dermatological Medicine)
We report a case of nonuremic calcific arteriolopathy (NUCA) in an 82-year-old Caucasian woman from rural Australia. The patient had no history of kidney disease or dialysis. NUCA is rare disease suspected on cutaneous and clinical features and diagnosed by characteristic findings on skin biopsy and vasculature imaging. Calcification induced microvascular occlusion in the absence of renal failure may not be immediately apparent. Clinical suspicion and appropriate investigations are essential for making a diagnosis. A diagnosis of NUCA may be missed given the rarity of the disease, and dermatologists and patients alike would benefit from a greater awareness of this disease.